On the Cognitive Function of Conceptual Metaphor: A Discourse Analytic Study of Obama’s Speech on ISIL - Zaidoon Abdulrazaq Abboud / Nagham Ja’far Hussein ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
Politics is a struggle for power. Political discourse is an important field of discourse analysis which includes different political forums such as debates and speeches. Politicians usually exploit certain strategies to convey their messages so as to persuade people with certain perspectives. They use language as a powerful tool that can be manipulated to control people’s mind, to gain the consent for their decisions and then to achieve their goals.  Actually, language may affect people’s thoughts, beliefs, perspectives and attitudes. In this study, American President Barack Obama’s speech on fighting ISIL has been analyzed. The aim of this paper is to reveal the role of language and to scrutinize the persuasive strategies and ideological components of Obama through using rhetorical devices especially metaphor to justify his decision of fighting ISIL. The present study is based on using Kövecses’ Model of Conceptual Metaphor in the analysis and interpretation of Obama’s speech concerning his request to congress for giving authorization of fighting ISIL.    The study of the cognitive function of metaphor is very important in comprehending such a political discourse.  Moreover, it is influential in analyzing andinterpreting Obama’s speeches concerning ISIL in many perspectives such as reflecting his policy and strategy in tackling, defying and destroying this terrorist group to disguise his hidden agenda and to gain the consent of public and American council opinions.